PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN ALUMUNIUM - Marshelly Chandra Kumala; Widodo (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
The objective of this is research was conducted to find out how the influence of the price and quality of products against customer loyalty at PT. Alakasa Extrusindo Jakarta. This research was conducted in Alakasa Extrusindo PT by doing data collection, through the primary data and secondary data. The research results showed that the simultaneous price variables and product quality has a positive and significant effect against the variable customer loyalty. partially showed that price variables has a positive and significant influence towards customer loyalty. And partially showed that product quality variables has a positive and significant influence towards customer loyalty .